Firstborn - Seidler, Tor (Atheneum Books for Young Readers, 2016)
Lamar, a young wolf in the Yellowstone pack led by Lamar's father, Blue Boy, struggles to balance his familial duties with his own destiny and his forbidden romance with a coyote.